Modifications to the k-kL-ω transition model based on Pohlhausen and Falkner-Skan profiles - Fürst, Jiri; Islam, Mazharul; Príhoda, Jaromír; Wood, David H. (2015)
We will present novel modifications of the three-equation k-kL-u: eddy viscosity model proposed by Walters and Cokljat [1] for the adverse pressure gradient flows that occur on wind turbine blades and airfoils. The original model was based on the k-u: framework with an additional transport equation for laminar kinetic energy which allows the prediction of natural or bypass laminar-turbulent transitions. The model uses only local information and is, therefore, easily implemented in modern CFD codes including Fluent and OpenFOAM. The original model shows very good agreement with experimental data for zero pressure gradient flows (see e.g. [1]) but it delays the transition for adverse pressure gradient flows at low free-stream turbulence levels [2]. Both stability analysis and experiments show that the pressure gradient has a big influence on transition [3]